2019
DOI: 10.3390/drones3010028
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Unmanned Aerial Vehicles to Survey Mesocarnivores

Abstract: With the widespread extirpation of top predators over the past two centuries, mesocarnivores play an increasingly important role in structuring terrestrial trophic webs. However, mesocarnivores are difficult to survey at a population level because their widely spaced territories and nocturnal behavior result in low detection probability. Existing field survey techniques such as track plates and motion-sensitive camera traps are time-consuming and expensive, and yet still yield data prone to systematic errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Miniaturization of thermal imaging cameras has made them light enough to be attached to UAVs, and these systems are potentially useful for surveying endothermic wildlife (Christiansen et al 2014). For example, Bushaw et al (2019) used a quadcopter UAV equipped with a thermal camera to locate and identify nocturnal mesocarnivores in southern Canada and reported being able to detect animals as small as rodents in grassy fields. Scholten et al (2019) used a UAV and thermal camera to locate small, well‐hidden field sparrow ( Spizella pusilla ) nests in grasslands in the northern United States, and Bushaw et al (2020) used a similar system to locate diving duck nests in prairie Canada.…”
mentioning
confidence: 99%
“…Miniaturization of thermal imaging cameras has made them light enough to be attached to UAVs, and these systems are potentially useful for surveying endothermic wildlife (Christiansen et al 2014). For example, Bushaw et al (2019) used a quadcopter UAV equipped with a thermal camera to locate and identify nocturnal mesocarnivores in southern Canada and reported being able to detect animals as small as rodents in grassy fields. Scholten et al (2019) used a UAV and thermal camera to locate small, well‐hidden field sparrow ( Spizella pusilla ) nests in grasslands in the northern United States, and Bushaw et al (2020) used a similar system to locate diving duck nests in prairie Canada.…”
mentioning
confidence: 99%
“…Recent weight reductions of thermal‐imaging cameras have allowed their attachment to UAVs, and these systems have been used to monitor wildfires (Ambrosia et al 2003), conduct search‐and‐rescue missions (Rudol and Doherty 2008), and survey wildlife (Haschberger 1996, Elsey and Trosclair 2016, Scholten et al 2019). UAVs and thermal‐imaging cameras have been used to detect large mammals, such as Roe deer ( Capreolus capreolus ) (Israel 2011) and chimpanzees ( Pan troglodytes ) (Van Andel et al 2015), and have also been found to reliably detect mesocarnivores in prairie landscapes (Bushaw et al 2019). Recently, UAVs and thermal‐imaging cameras have also been used to detect bird nests.…”
mentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs) are currently installed in wildlife monitoring, and it is often combined with thermal imaging (Bushaw et al, 2019). Spaan et al (2019) investigated the abundance of spider monkeys ( Ateles spp.…”
Section: Introductionmentioning
confidence: 99%